2013
DOI: 10.3892/ijo.2013.1909
|View full text |Cite
|
Sign up to set email alerts
|

Kaempferol induces autophagy through AMPK and AKT signaling molecules and causes G2/M arrest via downregulation of CDK1/cyclin B in SK-HEP-1 human hepatic cancer cells

Abstract: Kaempferol belongs to the flavonoid family and has been used in traditional folk medicine. Here, we investigated the antitumor effects of kaempferol on cell cycle arrest and autophagic cell death in SK-HEP-1 human hepatic cancer cells. Kaempferol decreased cell viability as determined by MTT assays and induced a G2/M phase cell cycle arrest in a concentration-dependent manner. Kaempferol did not induce DNA fragmentation, apoptotic bodies or caspase-3 activity in SK-HEP-1 cells as determined by DNA gel electrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
81
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(96 citation statements)
references
References 35 publications
7
81
1
1
Order By: Relevance
“…We further examined the effect of kaempferol and kaempferide on SOD1 aggregation by using a series of concentrations based on previous studies (Fig. 3C) 21, 22 . As results, kaempferol (from 0.3 µM to 10 µM) and kaempferide (from 5 µM to 50 µM) significantly decreased the aggregates.…”
Section: Resultsmentioning
confidence: 99%
“…We further examined the effect of kaempferol and kaempferide on SOD1 aggregation by using a series of concentrations based on previous studies (Fig. 3C) 21, 22 . As results, kaempferol (from 0.3 µM to 10 µM) and kaempferide (from 5 µM to 50 µM) significantly decreased the aggregates.…”
Section: Resultsmentioning
confidence: 99%
“…Kaempferol is a flavonol present in fruits and vegetables, including onions, kale, broccoli, apples, cherries, berries, tea and red wine (11,12). Kaempferol has many biological properties, including anti-cancer, antioxidant activity, antiinflammatory effects (12,21).…”
Section: Discussionmentioning
confidence: 99%
“…Kaempferol is a dietary flavonoid and is found in fruits and vegetables and in traditional Chinese medicines (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…In HT-29 colon cancer cells, the treatment of kaempferol (0–60 μM) provoked apoptosis by activating the death receptor pathway and mitochondrial pathway [109]. Another study in SK-HEP-1 human liver cancer cells found G 2 /M cell cycle arrest and autophagy following kaempferol treatment, which might be the result of the modulation of CDK1/cyclin B expression and AMPK and AKT signaling pathways [110]. Kaempferol induced apoptosis in MCF-7 breast cancer cells [111].…”
Section: Experimental Studiesmentioning
confidence: 99%